(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2026)
This study evaluates the structural and geotechnical aspects of raft foundation design for residential buildings, focusing on the influence of soil conditions on moments and shear forces. A comparative analysis between manual calculations and SAFE software revealed deviations due to variations in soil stiffness. Empirical correction factors (CFs) were developed using multiple linear regression to enhance manual design accuracy by incorporating subgrade modulus, raft thickness, and column spacing. These CF were integrated into a Visual Basic for Applications (VBA)-based spreadsheet-based design tool, ensuring compliance with Eurocode standards. The tool demonstrated quantifiable accuracy, achieving percentage errors below 10% for critical positive moment (Mmax) and maximum shear forces (Vmax), particularly in medium to hard soils. Slightly higher errors were observed in soft soils, as CFs were weighted more towards stiffer soils. Discrepancies are present across all soil types for negative moments (Mmin) due to the limitations in conventional slab method assumptions in capturing the location of hogging moments in raft foundations. This outcome indicated the need for further refinement of CFs, possibly through the integration of additional empirical data. As the scope of this study is limited to residential buildings, future work could expand the applicability of this tool to high-rise buildings, which require more complex load distributions and additional soil parameters for accurate soil behaviour modelling. Enhancements could include consideration for various soil types with differing bearing capacities and settlement characteristics under load. Additionally, incorporating differential settlement analysis would improve the representation of raft foundation behaviour and extend the applicability of this tool to more complex geotechnical conditions. Overall, the tool remains a practical and efficient solution for early-stage design and verification against the Finite Element Method (FEM) results.